An embouchure aid for saxophone player - Ho-Jin Moon (Korean Academy of Conservative Dentistry, 2012)
This study aims to introduce the method that can relieve vibrating forces to oral environment by making an embouchure aid. Thin plastic crown forms were fabricated to prevent tooth abrasion and irritation to lip mucosa for the saxophone player. After application to the player, the most comfort form was chosen and delivered to 3 professional saxophone players. After 5 mon, the players responded to the survey. This embouchure aid did not disturb playing and gave comfort to lower lip. In general, the players preferred thin soft type and thought it caused little effect on sound. Far too little attention has been paid to the problems encountered by single-reed wind instrumentalist who suffer from tooth abrasion and irritation to lip mucosa. The embouchure aid not only prevent tooth damage but also diminish the discomfort of tight embouchure.